PENELITIAN HUBUNGAN PENDALAMAN KONSEP KARAKTER DI GAME ‘PERSONA 5’ DENGAN PERINGANAN MASALAH DEPRESI DI KALANGAN ANAK MUDA - Arnaldo Kendrick Demetrio; Muhammad Adi Sukma Nalendra (JURNAL RUPA MATRA, 2022)
Mental illness had become a problem that needs to be paid attention to in young adults, moreover on the concerning numbers of depressed young adults and the absence of an exact solution for young adults to solve depression on young adults. That’s why it is a need of a solution that is more lenient but effective, and that is game. Game by itself is a media that is appropriate for young adults, of some of it’s benefits to relieve stress, as a coping mechanism, and as a form of therapy to ease depression. The purpose of the research is to study the connection between the characters that are in the game Persona 5 on relieving depression-type mental illness for depressed young adults. The research method to gain data is by using descriptive qualitative research methods such as literature study to fulfill the main foundation data on the topic, and also by interviewing potential source person, giving a questionnaire to respondents related to the problem, and doing participative observation to the research participant. The result of the research shows that the game Persona 5 has characters that can make players relate to them so that the feelings that were previously hard to express can be opened and healed